2022
DOI: 10.1021/acs.chemmater.1c04042
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Ligand-Controlled Enhancement of Carrier Density in Plasmonic Tungsten Oxide Nanocrystals: Spectroscopic Observation of Trap-State Passivation via Multidentate Metal Phosphonate Bonding

Abstract: The localized surface plasmon resonance (LSPR) properties of nanocrystals (NCs) allow manipulation of optical responses by controlling their morphology, free carrier density, and local dielectric environment. In this context, semiconductor NCs, in which plasmonic properties arise due to various types of doping, provide unique opportunities in tailoring LSPR properties for a wide range of applications as viable alternatives to expensive noble metal NCs. Although extensive works have been done to control the LSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 94 publications
2
25
0
Order By: Relevance
“…32,33 We showed that TD-PA is a unique surface passivating ligand that not only increased the passivation sites per ligand compared to alkylcarboxylate ligands allowing greater passivation of undercoordinated near-neighbor tungsten atoms in highly deficient WO 3−x NPLs but also substantially improved the LSPR properties of colloidal WO 3−x NPLs. 30 Our selected ligands, Ethyl-PA, Phenyl-PA, and NO 2 -BA provide a wide variety of structural diversity such as length of the alkyl chain, conjugation, and electron-withdrawing substitution. Colloidal synthesis and ligand exchange of WO ) and carboxylate (−CO 2 − ) binding head groups (i.e., TD-PA and MA); (2) ligands with different backbones but an identical, −PO 3 2− binding head group (i.e., TD-PA, Phenyl-PA, and Ethyl-PA); and (3) ligands with aromatic πconjugation but two different binding head groups (i.e., NO 2 -BA and Phenyl-PA).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…32,33 We showed that TD-PA is a unique surface passivating ligand that not only increased the passivation sites per ligand compared to alkylcarboxylate ligands allowing greater passivation of undercoordinated near-neighbor tungsten atoms in highly deficient WO 3−x NPLs but also substantially improved the LSPR properties of colloidal WO 3−x NPLs. 30 Our selected ligands, Ethyl-PA, Phenyl-PA, and NO 2 -BA provide a wide variety of structural diversity such as length of the alkyl chain, conjugation, and electron-withdrawing substitution. Colloidal synthesis and ligand exchange of WO ) and carboxylate (−CO 2 − ) binding head groups (i.e., TD-PA and MA); (2) ligands with different backbones but an identical, −PO 3 2− binding head group (i.e., TD-PA, Phenyl-PA, and Ethyl-PA); and (3) ligands with aromatic πconjugation but two different binding head groups (i.e., NO 2 -BA and Phenyl-PA).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The lateral dimensions of NPLs are determined to be ∼14 and 4.7 nm in length and width, respectively (Figure 1B,C). Based on our recent work, 30 we do not anticipate any morphological changes in the NPL during the ligand treatment. We used purified samples to prepare thin films.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations